The Therapeutic Effects of DDP/CD44-shRNA Nanoliposomes in AMF on Ovarian Cancer - Guo, Ting; Zhu, Yinxing; Yue, Miao; Wang, Fujin; Li, Zhifeng; Lin, Mei (Frontiers in Oncology, 2022)
Background Globally, ovarian cancer is one of the most common gynecological malignant tumors, and the overall curative effect has been unsatisfactory for years. Exploring and investigating novel therapeutic strategy for ovarian cancer are an imperative need. Methods Using manganese zinc ferrite nanoparticles (PEG-MZF-NPs) as gene transferring vector and drug delivery carrier, a new combinatorial regimen for the target treatment of ovarian cancer by integrating CD44-shRNA, DDP (cisplatin) and magnetic fluid hyperthermia (MFH) together was designed and investigated in vivo and in vitro in this study. Results PEG-MZF-NPs/DDP/CD44-shRNA nanoliposomes were successfully prepared, and TEM detection indicated that they were 15–20 nm in diameter, with good magnetothermal effect in AMF, similar to the previously prepared PEG-MZF-NPs. Under the action of AMF, PEG-MZF-NPs/shRNA/DDP nanoliposomes effectively inhibited ovarian tumors’ growth, restrained the cancer cells’ proliferation and invasion, and promoted cell apoptosis. VEGF, survivin, BCL-2, and BCL-xl proteins significantly decreased, while caspase-3 and caspase-9 proteins markedly increased both in vitro and in vivo, far better than any of the individual therapies did. Moreover, no significant effects were found on bone marrow hematopoiesis and liver and kidney function of nude mice intervened by the combinatorial therapeutic regimen. Conclusion In the present study, we developed PEG-MZF-NPs/DDP/CD44-shRNA magnetic nanoliposomes and inaugurated an integrated therapy through the synergistic effect of MFH, gene therapy, and chemotherapy, and it shows a satisfactory therapeutic effect on ovarian cancer in vitro and in vivo, much better than any single treatment regimen did, with no significant side effects. This study provides a new promising method for ovarian cancer treatment.